Confirmation, Characterization, and Management of Glyphosate-Resistant Ragweed Parthenium (Parthenium hysterophorus L.) in the Everglades Agricultural Area of South Florida. (June 2015) - Fernandez, Jose V.; Odero, Dennis C.; MacDonald, Gregory E.; Ferrell, Jason; Gettys, Lyn A.
Abstract : Growers have observed lack of control of ragweed parthenium with glyphosate at 0.84 kg ae ha −1 used for weed control in noncrop areas and fallow fields in the Everglades Agricultural Area (EAA) of South Florida. Therefore, studies were conducted to (1) confirm and characterize the level of glyphosate resistance in ragweed parthenium from the EAA, (2) determine if reduced absorption or translocation is the mechanism of resistance of ragweed parthenium to glyphosate, and (3) evaluate the efficacy of POST herbicides commonly used in cultivated and noncrop areas for broadleaf weed control on flowering ragweed parthenium at the full and half labeled rate. A dose-response bioassay was used to determine the response of the rosette ragweed parthenium biotype from the EAA (resistant) and a susceptible biotype from Stoneville, MS, to glyphosate. The bioassay showed that the resistant biotype was 40- to 43-fold less sensitive to glyphosate when compared to the susceptible biotype. There was no significant difference in glyphosate absorption or translocation from the treated leaf to the rest of the plant 168 h after treatment between resistant and susceptible biotypes. This shows that absorption or translocation is not a mechanism of glyphosate resistance by ragweed parthenium. Saflufenacil + dimethenamid-P and hexazinone provided rapid and complete control of flowering ragweed parthenium 3 wk after treatment (WAT). Aminocyclopyrachlor + chlorsulfuron and aminopyralid at the full and the half label rates provided 100% control of ragweed parthenium by 9 WAT. Clopyralid, 2, 4-D amine, and glufosinate at the full label rate provided 89 to 98% control of ragweed parthenium 9 WAT. Control of ragweed parthenium 9 WAT was < 75% with flumioxazin, fomesafen, glyphosate, imazapic, imazethapyr, mesotrione, oxyfluorfen, and paraquat, irrespective of use rate.